Mechanically evolving and solvent-responsive waste-valorized poly (methacrylated β-keratin) organogel nanostructures and exogel spatiotemporal transition property - Yoobsan Ejeta Amensisa; Chia-Kuan Lin; Chih-Chia Cheng; Chang-Mou Wu; Chien-Hsing Lu; Jem-Kun Chen (Chemical Engineering Journal, 2026)

Infragravity oscillations in a coupled-basin marina under typhoon conditions: physical model experiments and numerical modeling - Shih-Feng Su; Chia-Hsuan She; Jia-Lin Chen; Chen-Hsun Wei; Zhi-Cheng Huang (Ocean Engineering, 2026)

Mobilized-clay-driven toppling: A new mechanism resolving the “energy paradox” of under-dip slope failure in flysch terrains - Thanh-Tùng Nguyễn; Ivo Baroň; Filip Hartvich; Jiří Havlík; Lenka Kociánová; Jan Klimeš; Jan Černý; Martin Šutjak; Václav Dušek; Cheng-Han Lin; Chia-Han Tseng; Yi-Chin Chen; et al. (Landslides, 2026)

Caffeinated chewing gum improves military performances in special forces soldiers - Yi-Jie Shiu; Che-Hsiu Chen; Hung-Yu Lin; Chia-Cheng Yang; Chi-Wen Yen; Han-Yuan Chang; Hsuan-Ta Chen; Chih-Hui Chiu (European Journal of Applied Physiology, 2026)

Fine-scale post-fire forest recovery patterns and compound drivers in Taiwan’s high-mountain national parks - Chu-Chia Kuo; Yu-Ling Liu; Cheng-Tao Lin (Forest Ecology and Management, 2026)

Ensemble learning: a study on the border inspection prediction model for high-risk products adulterated with Sudan Red in Taiwan - Li-Ya Wu; Wei-Chih Cheng; King-Fu Lin; Jia-Jhen Lee; Wen-Chou Lin; Hsu-Yang Lin; Chia-Yen Lu; Chih-Kang Chiang (Food Control, 2026)

Serum albumin and uric acid: biomarkers of neurocognitive and physical function in early Parkinson’s disease - Cheng-Liang Chang; Tsu-Kung Lin; Chia-Liang Tsai (Experimental Brain Research, 2026)

Inhibitory activity of dehulled adlay extrudate against ethanol-induced gastric mucosal injury and stability tests of active indicative components - Ming-Yi Lee; Shih-Min Hsia; Ching-I Lin; Yu-Chia Chang; Yi-Hsiang Liang; Lu-Chi Chan; Ju-Tsui Lin; Yi-Fen Chiang; Wei-Chih Sun; Cheng-Pei Chung (Journal of Cereal Science, 2026)

Paleo-landslide analysis reveals underestimated seismic hazards in the outer Western Carpathians - Thanh-Tùng Nguyễn; Ivo Baroň; Rostislav Melichar; Jia-Cian Gao; Filip Hartvich; Cheng-Han Lin; Jan Klimeš; Martin Šutjak; Lenka Kociánová; Václav Dušek; František Bárta; Chia-Han Tseng; et al. (Engineering Geology, 2026)

Coupled oxygen and nitrogen defect sites in Co-N4-coordinated frameworks facilitate stepwise CO2 methanation - Pin-Yu Liu; Sheng-Xiang Chou; Wei-Tse Sun; Hsin-Han Chen; Cheng-Hung Tsai; Yen-Lin Lai; Yu-Cheng Shao; Chi-Liang Chen; Yu-Ching Huang; Yun-Wei Chiang; Bo-Hong Liu; Chia-Hsin Wang; et al. (Chemical Engineering Journal, 2026)

Correction to: Determination of critical power in trained rowers using a three-minute all-out rowing test - Ching-Feng Cheng; Yi-Shan Yang; Hui-Mei Lin; Chia-Lun Lee; Chun-Yi Wang (European Journal of Applied Physiology, 2026)

Dexmedetomidine Mitigates Sevoflurane-Induced Neurodevelopmental Effects in Paediatric Anaesthesia: A Meta-Analysis and Preclinical Study - Hsuan-Chih Lao; Chia-Wei Huang; Ssu-Han Wang; Yen-Lin Su; Chien-Hui Chang; Cheng-Yen Liao; Jen-Chieh Wu; Ying-Chun Lin; Jin-Wu Tsai (Journal of Neuroimmune Pharmacology, 2026)
Sevoflurane (Sevo) anaesthesia in children is linked to an increased incidence of postoperative emergence agitation (EA) and potential neurotoxicity in developing brains. However, the specific risks of subanaesthetic foetal or neonatal exposure to Sevo remain unclear. This study evaluates the safety and efficacy of combining dexmedetomidine (Dex) with Sevo to manage EA in paediatric anaesthesia. A systematic review and meta-analysis of randomized controlled clinical trials involving children under 8 years old revealed that Dex significantly reduces EA incidence when administered via intravenous, perineural, and intranasal routes. Using in utero electroporation, we found that pregnant mice exposed to 2.5% Sevo at embryonic days 14.5 and 15.5 exhibited transient neuronal migration deficits, with 25% of neurons delayed in deeper cortical layers. However, these neurons migrated to the cortex by postnatal day 8. Neonatal mice exposed to 2.5% Sevo experienced a 10% reduction in dendritic spine density in adolescence, associated with impaired somatosensory function, as assessed by the Von Frey test. Remarkably, Dex pretreatment ameliorated these pathological and functional changes. Thus, foetal or neonatal Sevo exposure can delay neuronal migration and reduce dendritic spine density. Dex co-administration effectively mitigates these adverse outcomes, supporting its potential use in paediatric anaesthesia to protect developing brains. Graphical abstract

Disease outbreaks substantially enhance greenhouse gas emissions from Asian seabass (Lates calcarifer) aquaculture pond - Han-Yang Yeh; Chien-Wei Tu; Yi-Jung Chen; Wen-Ping Cheng; Pei-Yu Shih; Chia-Chia Yu; Wei-Sheng Zhang; Wei-En Hung; Yu-Ru Lin; Zhen Hao Liao; Wen-Chen Chou; Hsiao-Chun Tseng; et al. (Marine Pollution Bulletin, 2026)

Dibifree, a dietary phytomix, improves glycemic control and adiposity via modulation of the gut–pancreas–adipose–immune axis in type 2 diabetes - Tzu-Yi Huang; Niann-Tzyy Dai; Hsiu-Jung Liao; Ly Hien Doan; Tai-Shan Cheng; Wen-Yu Hsieh; I-Hsuan Lin; Yu-Tang Huang; Chia-Ching Liaw; Hsiao-Sheng Liu; Wei-Ming Cheng; Chun-Li Su; et al. (Food Research International, 2026)

STAT3 Signaling Mediates Agomelatine Restoration of Prefrontal Cortex Synaptic Plasticity in Chronic Social Defeat Stress Mice - Chi-Wei Lee; Han-Fang Wu; Hsin-Ju Yen; Lun-De Liao; Wei-Chang Mao; Hsun-Shuo Chang; Yih-Fung Chen; Chia-Hsien Lin; Cheng-Ta Li; Hui-Ching Lin (Molecular Neurobiology, 2026)
Major depressive disorder (MDD) is a major public health issue worldwide. It not only causes an increased socio-economic burden, but also negatively affects personal lives. It has been shown that depression leads to impairments in synaptic plasticity, such as impaired long-term potentiation (LTP) in the prefrontal cortex (PFC). A recent study reported that administration of agomelatine, a melatonin receptor agonist and 5-hydroxytryptamine (5-HT) 2C antagonist, which may be involved in synaptic functions, for 1 week has a rapid antidepressive effect. Moreover, the mechanism of Glycogen synthase kinase 3β (GSK3β), regulated by signal transducer and activator of transcription 3 (STAT3), may play an important role in the synapse-related pathological mechanisms of depression. Hence, we used chronic social defeat stress (CSDS) as an animal model of depression, to investigate whether synaptic plasticity impairment in depression, improved by agomelatine, is mediated through the STAT3 mechanism. The results showed that depressive-like behaviors were reversed after 1 week of agomelatine treatment. Moreover, the impairment of LTP and alteration of spine density were reversed by agomelatine in the PFC. We further applied AG490, an inhibitor of STAT3, to demonstrate that the therapeutic mechanism of agomelatine improves synaptic plasticity through STAT3-regulated phosphorylation of GSK3β. Taken together, these results demonstrated that STAT3-regulated downstream molecules are potential therapeutic targets for the rapid action of antidepressants.

Pilot study on integrating multidisciplinary technologies to implement an autonomous and smart harvester for asparagus - Joe-Air Jiang; Jen-Cheng Wang; Hung-Jen Lin; Cheng-Ying Chou; Chia-Chun Chien; Wei-Hao Huang; An-Chi Liu; Cheng-Chun Lee; Ming-Chi Guo; Jui-Chu Peng (Computers and Electronics in Agriculture, 2025)

Population structure of Tachypleus tridentatus in Xiamen Bay: Proposing a network of transboundary marine protected areas - Yi-Hua Jin; Yi-Jia Shih; Hsin-I. Lin; Ya-Hui Chen; Yung-Sheng Cheng; Chia-Fa Lee; Yang-Chi Chang; Yi Chang (Regional Studies in Marine Science, 2025)

Hydrogeochemical characteristics and the monitoring from 2020 to 2023 of hot spring waters in Tatun Volcanic Group, Taiwan - Ju-lien Pi; Hsueh-Yu Lu; Hsiao-Fen Lee; Hung-Chun Chao; Chen-Feng You; Tsung-Ren Peng; Raymond Patrick R. Maximo; Chia-Tai Wu; Ya-Wen Wu; Chung Fang; Cheng-Horng Lin (Journal of Asian Earth Sciences, 2025)

Interplay of plasma-treated BiVO4 photoanode and CoFe metal organic frameworks enabled synergistic photoelectrochemical water splitting - Zhi-Cheng Yan; Min-Ho Lin; Chen-Hao Yeh; Pei-Lun Chen; Jun Song Chen; Po-Hsuan Hsiao; Chia-Yun Chen (Chemical Engineering Journal, 2025)

Analytical and usability comparison of microsampling dried blood spot devices for glucocorticoid detection in sports using ultra-high-performance liquid chromatography–tandem mass spectrometry - Cheng-Chia Chen; Yu-En Lin; Mei-Chich Hsu; Yu-Chuan Lin; William Chih-Wei Chang (Analytica Chimica Acta, 2025)

Characterization of neutral fluids in the volcanic geothermal system under the Tatun Volcano Group, Taiwan - Yi-Chia Lu; Chyi Wang; Sheng-Rong Song; Pei-Ling Wang; Ting-Jui Song; Sachihiro Taguchi; Tsung-Ren Peng; Li-Hung Lin; Jian-Cheng Lee; Hong-Chun Li (Journal of Geochemical Exploration, 2025)

Integrated assessment of wind energy's emission and meteorological effects on PM2.5 in Taiwan - I-Chun Tsai; Pei-Rong Hsieh; Cheng-Wei Lin; Chung-Cheh Chou; Chia-Ying Tu; Chao-Tzuen Cheng; Huang-Hsiung Hsu (Journal of Environmental Management, 2025)

Light-capture capability based flexible negative pyramid microarrays coated with silver nano-islands for SERS detection - Chia-Hsien Lin; Yun-Chu Chen; Kuan-Syun Wang; Ding-Jia Yueh; Shih-Hsien Yeh; Jeng-Shiung Chen; Yung-Hsin Cheng; Yuh-Lin Wang; Ting-Yu Liu (Chemical Engineering Journal, 2025)

Manipulation of carbon dioxide adsorption and desorption via CO₂-philic fibrous polyethyleneimines under alternating current electric fields by frequency tuning - Chih-Wei Chen; Yi-Hua Lin; Chih-Chia Cheng; Chien-Hsing Lu; Jem-Kun Chen (Science of The Total Environment, 2025)

Monitoring for classical swine fever virus persistence and seropositivity in vaccinated pig farms using on-farm sentinel pigs during the pre-elimination phase toward a CSF-free status - Kuo-Jung Tsai; Hui-Yu Chen; Chun Wang; Chung-Shun Hung; Wei-Cheng Hsu; Tsu-Han Chen; Ming-Chung Deng; Cheng-Ta Tsai; Nien-Nong Lin; Jung-Pin Hsu; Chia-Yi Chang; Yu-Liang Huang (Preventive Veterinary Medicine, 2025)

Functional oligosaccharides derived from the degradation of natural Dendrobium polysaccharides by human gut microbes regulate physiological factors associated with type-2 diabetes - Ming-Che Cheng; Hsi-Mei Chen; Bao-Jiun Bai; Tsu-Yuan Chang; Meng-Chin Chen; Yen- Ting Lin; Chi-Kung Ni; Mei-Kuang Lu; Hui-Kang Liu; Chia-Chuan Chang (Phytochemistry Letters, 2025)

Interfacial engineering meets process optimization: Highly stable silicon-graphite anodes via pre-calendering polyvinylidene difluoride-MgO coatings - Chu-Chun Lin; Cheng-Che Chien; Yu-Ting Weng; Chia-Chen Fang; Nae-Lih Wu; Rainer Adelung; Mozaffar Abdollahifar; Ryo Takata; Carlos Eduardo Alarcón-Suesca; Franz Schmidt (Chemical Engineering Journal, 2025)

Localized Trefftz method for wave generation and propagation in a two-dimensional numerical wave tank - Xiran Lin; Liangbin Xu; Yan-Cheng Liu; Chia-Ming Fan (Ocean Engineering, 2025)

Dynamic weather-based scheduling for achieving energy savings in factories - Kung-Yueh Camyale Chao; Yi-Ting Liu; Chia-Yi Lee; Ji-Hong Lin; Chia-Ping Cheng; Ming-Hao Lee; Hung-Chi Kuo; Tai-Jen George Chen (Energy and Buildings, 2025)

High sensitivity mercury ion detection via thermal shock and quench with molecular sieve-functionalized FETs - Guan-Cheng Zeng; Hsuan-Wei Huang; Chia-Kai Lin; Jung-Chih Chen; Sheng-Chun Hung; Guo-Chun Dong; Yu-Lin Wang (Chemical Engineering Journal, 2025)

Microbiological Activity and Oxygen Availability Influence Arsenic Mobilization and Redox Transformation in an Arsenic-Rich Aquifer - Yu-Chen Su; Yu-Ju Chu; Chia-Cheng Wei; Chan-Wei Yu; Pei-Ling Yen; Yu-Hsuan Kuo; Ting-An Lin; Vivian Hsiu-Chuan Liao (Exposure and Health, 2025)

Pathotyping and molecular serotyping of clinical isolates of Glaesserella parasuis in Taiwan - Wei-Hao Lin; Chia-Hung Yen; Cheng-Yao Yang; Chuen-Fu Lin; Yung-Fu Chang; Chao-Nan Lin; Ming-Tang Chiou (Brazilian Journal of Microbiology, 2025)

Highly active Cu-embedded in magnetic carbon nanofibers for the reduction of 4-nitrophenol - Ching-Shiun Chen; Tse-Ching Chen; Kai-Lin Chiu; Cheng-Rong Hsing; Li-Yu Wang; Chia-Min Yang; Chih-Wen Pao; Chi-Liang Chen (Chemical Engineering Journal, 2025)

Using Gaussian Mixture Model Clustering for the Automated Segmentation of Cerebral Arteriovenous Malformations in Magnetic Resonance Images - Ting-Yu Lin; Cheng‑Chia Lee; Yu-Wei Chen; Hsiu-Mei Wu; Ching-Jen Chen; Huai-Che Yang; Syu-Jyun Peng (Journal of Medical and Biological Engineering, 2025)

Performance of Convolutional Neural Network Models in Meningioma Segmentation in Magnetic Resonance Imaging: A Systematic Review and Meta-Analysis - Ting-Wei Wang; Jia-Sheng Hong; Wei-Kai Lee; Yi-Hui Lin; Huai-Che Yang; Cheng-Chia Lee; Hung-Chieh Chen; Hsiu-Mei Wu; Weir Chiang You; Yu-Te Wu (Neuroinformatics, 2024)
Background Meningioma, the most common primary brain tumor, presents significant challenges in MRI-based diagnosis and treatment planning due to its diverse manifestations. Convolutional Neural Networks (CNNs) have shown promise in improving the accuracy and efficiency of meningioma segmentation from MRI scans. This systematic review and meta-analysis assess the effectiveness of CNN models in segmenting meningioma using MRI. Methods Following the PRISMA guidelines, we searched PubMed, Embase, and Web of Science from their inception to December 20, 2023, to identify studies that used CNN models for meningioma segmentation in MRI. Methodological quality of the included studies was assessed using the CLAIM and QUADAS-2 tools. The primary variable was segmentation accuracy, which was evaluated using the Sørensen–Dice coefficient. Meta-analysis, subgroup analysis, and meta-regression were performed to investigate the effects of MRI sequence, CNN architecture, and training dataset size on model performance. Results Nine studies, comprising 4,828 patients, were included in the analysis. The pooled Dice score across all studies was 89% (95% CI: 87–90%). Internal validation studies yielded a pooled Dice score of 88% (95% CI: 85–91%), while external validation studies reported a pooled Dice score of 89% (95% CI: 88–90%). Models trained on multiple MRI sequences consistently outperformed those trained on single sequences. Meta-regression indicated that training dataset size did not significantly influence segmentation accuracy. Conclusion CNN models are highly effective for meningioma segmentation in MRI, particularly during the use of diverse datasets from multiple MRI sequences. This finding highlights the importance of data quality and imaging sequence selection in the development of CNN models. Standardization of MRI data acquisition and preprocessing may improve the performance of CNN models, thereby facilitating their clinical adoption for the optimal diagnosis and treatment of meningioma.

Changes in the small-molecule fingerprints of rice planted near an industrial explosion site in Taiwan - Wen-Ling Chen; Husan-Yu Tai; Chang-Chuan Chan; Hung-Chien Lin; Ting-Hsuan Hung; Mong-Hsun Tsai; Chia-Cheng Wei; Yu-San Han; Chuan-Chou Shen (Environmental Science and Pollution Research, 2024)

Nanoplastics indirectly compromise lettuce growth in hydroponic systems via microbial extracellular vesicles derived from Curvibacter fontanus - Bao-Hong Lee; Yi-Ching Lin; Yu-Juan Zheng; Tang-Long Shen; Ting-Yu Cheng; Chih-Chia Huang; Wei-Hsuan Hsu (Journal of Hazardous Materials, 2024)

Protective effects of nordalbergin against LPS-induced endotoxemia through inhibiting MAPK/NF-κB signaling pathway, NLRP3 inflammasome activation, and ROS production - Pin-Rong Chen; Chia-Yang Li; Taha Yazal; I-Chen Chen; Po-Len Liu; Yi-Ting Chen; Ching-Chih Liu; Jung Lo; Tzu-Chieh Lin; Ching-Tang Chang; Hsin-En Wu; Yuan-Ru Chen; et al. (Inflammation Research, 2024)

The changes and the potential clinical applications of cytokines in Taiwan’s major venomous snakebites patients - Chih-Chuan Lin; Chia-Cheng Wang; Chun-Hsiang Ou Yang; Chien-Chun Liu; Jau-Song Yu; Wen-Chih Fann; Yen-Chia Chen; Chia-Pang Shih (Toxicon, 2024)

Impacts of ship emissions and sea-land breeze on urban air quality using chemical characterization, source contribution and dispersion model simulation of PM2.5 at Asian seaport - Yu-Lun Tseng; Wen-Hsi Cheng; Chung-Shin Yuan; Kuo-Cheng Lo; Chitsan Lin; Chia-Wei Lee; Gerry Bagtasa (Environmental Pollution, 2024)

Impact of occupational noise exposure on the hearing level in hospital staffs: a longitudinal study - Tang-Chuan Wang; You-Cheng Yu; Alan Hsu; Jia-Yi Lin; Yung-An Tsou; Chiu-Shong Liu; Kai-Jen Chuang; Wen-Chi Pan; Chin-An Yang; Sung-Lin Hu; Chien-Yi Ho; Tzu-Liang Chen; et al. (Environmental Science and Pollution Research, 2024)

Inhibition of continuous cropping obstacle of celery by chemically modified biochar: An efficient approach to decrease bioavailability of phenolic allelochemicals - Chia-Chia Lin; Yu-Ting Liu; Po-Hsiang Chang; Yi-Cheng Hsieh; Yu-Min Tzou (Journal of Environmental Management, 2023)

Retail location modeling of supermarket chains in Taipei city - Pei-Chun Lin; T.C. Edwin Cheng; Chia-Hui Hsu (Applied Geography, 2023)

Miticidal activity of Photorhabdus luminescens for controlling two spider mites, Tetranychus urticae and Tetranychus kanzawai, in Carica papaya - Tzay-Tien Hsieh; Ju-Chun Chang; Chienyan Hsieh; Jui-Tang Tseng; Show-Jow Lin; Cheng-Ju Yang; Feng-Chia Hsieh; Yu-Shin Nai (BioControl, 2023)

Association of mono-2-ethylhexyl phthalate with adverse outcomes in chronic hemodialysis patients - Chia-Lin Wu; Yu-Wei Fang; Yi-Chou Hou; Kuo-Cheng Lu; Wen-Hsin Tsai; Ping-Hsun Lu; Tzong-Shyuan Lee; Ko-Lin Kuo (Environmental Science and Pollution Research, 2023)
Phthalate exposure is widespread and has a global impact. Growing evidence shows that mono-2-ethylhexyl phthalate (MEHP) exposure has a negative impact on human health. However, whether MEHP exposure is associated with mortality and other adverse outcomes in hemodialysis patients remains unknown. This study prospectively enrolled 217 patients on maintenance hemodialysis from June 30, 2021, to August 16, 2022. Baseline serum MEHP, di-2-ethylhexyl phthalate (DEHP), and indoxyl sulfate (IS) concentrations were measured. Primary endpoints were all-cause mortality or composite adverse outcomes, including all-cause death plus hospitalization due to cardiovascular disease, heart failure, stroke, infection, or cancer. Serum MEHP concentrations were positively associated with DEHP but not indoxyl sulfate concentrations in hemodialysis patients. Additionally, serum MEHP concentrations were significantly and independently associated with all-cause mortality and composite adverse outcomes (adjusted hazard ratios [HRs], 1.04 and 1.03 per ng/mL, 95% confidence intervals [CIs], 1.01–1.07 and 1.00–1.05; p = 0.016 and 0.015, respectively). We found a cutoff value of MEHP for predicting both endpoints. Patients with serum MEHP concentrations of ≥ 41.8 ng/mL had much higher risks for all-cause mortality and composite adverse outcomes (adjusted HRs, 39.2 and 13; 95% CIs, 2.44–65.7 and 2.74–61.4; p = 0.011 and 0.001, respectively). MEHP exposure is significantly associated with higher risks for all-cause mortality and composite adverse outcomes. Hemodialysis patients with serum MEHP concentrations above 41.8 ng/mL had much poorer prognoses regarding both outcomes.

Seasonal Disparities of Human Health Risk and Particle-Bound Metal Characteristics Associated with Atmospheric Particles in a Fishery Harbor - Cheng-Yun Tsai; Yen-Ping Peng; Chia-Hua Lin; Ku-Fan Chen; Chia-Hsiang Lai; Pin-Hao Qiu (Archives of Environmental Contamination and Toxicology, 2023)

Applicability of carbonate clumped isotope thermometry in the Tuchang-Jentse geothermal field - Yi-Chia Lu; Sheng-Rong Song; Ling-Wen Liu; Tsung-Ren Peng; Bill Bing-Cheng Chen; Remy Kai-Cheng Tu; Li-Hung Lin; Pei-Ling Wang (Geothermics, 2023)

Rice OsHsp16.9A interacts with OsHsp101 to confer thermotolerance - Yi-Hsin Liu; Tong-Seung Tseng; Ching-Rong Wu; Shu-Ting Cho; Chih-Horng Kuo; Xin-Jie Huang; Jung-Yi Cheng; Kuo-Hsuan Hsu; Kung-Fu Lin; Chia-Chin Liu; Ching-Hui Yeh (Plant Science, 2023)

Selective accumulation of ionic nanocrystal H2 storage system as an in situ H2/boric acid nanogenerator fights against ethanol-induced gastric ulcers - Chih-Wei Chou; Wei-Tso Chia; Cam-Hoa Mac; Cheng-Yu Wu; Chun-Chieh Chen; Hsiang-Lin Song; Yi-Hsuan Lin; Yu-Jung Lin; Hsing-Wen Sung (Chemical Engineering Journal, 2023)

Genomic architecture underlying morphological and physiological adaptation to high elevation in a songbird - Chia‐Wei Lu; Shih‐Ting Huang; Shun‐Jen Cheng; Chen‐Tau Lin; Yu‐Cheng Hsu; Cheng‐Te Yao; Feng Dong; Chih‐Ming Hung; Hao‐Chih Kuo (Molecular Ecology, 2023)
Organisms often acquire physiological and morphological modifications to conquer ecological challenges when colonizing new environments which lead to their adaptive evolution. However, deciphering the genomic mechanism of ecological adaptation is difficult because ecological environments are often too complex for straightforward interpretation. Thus, we examined the adaptation of a widespread songbird—the rufous‐capped babbler ( Cyanoderma ruficeps )—to a relatively simple system: distinct environments across elevational gradients on the mountainous island of Taiwan. We focused on the genomic sequences of 43 birds from five populations to show that the Taiwan group split from its sister group in mainland China around 1–2 million years ago (Ma) and colonized the montane habitats of Taiwan at least twice around 0.03–0.22 Ma. The montane and lowland Taiwan populations diverged with gene flow between them, suggesting strong selection associated with different elevations. We found that the montane babblers had smaller beaks than the lowland ones, consistent with Allen's rule, and identified candidate genes— COL9A1 and SOX11 —underlying the beak size changes. We also found that altitudinally divergent mutations were mostly located in noncoding regions and tended to accumulate in chromosomal inversions and autosomes. The altitudinally divergent mutations might regulate genes related to haematopoietic, metabolic, immune, auditory and vision functions, as well as cerebrum morphology and plumage development. The results reveal the genomic bases of morphological and physiological adaptation in this species to the low temperature, hypoxia and high UV light environment at high elevation. These findings improve our understanding of how ecological adaptation drives population divergence from the perspective of genomic architecture.

Toward sustainable inland aquaculture: Coastal subsidence monitoring in Taiwan - Wei-Chia Hung; Cheinway Hwang; Luigi Tosi; Shao-Hung Lin; Pei-Ching Tsai; Yi-An Chen; Wei-Ji Wang; En-Cheng Li; Sihao Ge (Remote Sensing Applications: Society and Environment, 2023)

Effect of species, muscle location, food processing and refrigerated storage on the fish allergens, tropomyosin and parvalbumin - Chia-Lin Tsai; Kristy Perng; Yu-Chen Hou; Cheng-Jou Shen; I-Ning Chen; Yi-Tien Chen (Food Chemistry, 2023)

Analyzing landslide-induced debris flow and flow-bridge interaction by using a hybrid model of depth-averaged model and discrete element method - Wen-Jie Shiu; Ching-Fang Lee; Chia-Chi Chiu; Meng-Chia Weng; Che-Ming Yang; Wei-An Chao; Chun-Yuan Liu; Cheng-Han Lin; Wei-Kai Huang (Landslides, 2023)

Assessing consumer perceptions of chemical leasing business models and possibilities for adoption by Taiwanese manufacturers - Chen-Fu Lu; Chia-Yi Cheng; Ying-Lin Hung (Sustainable Production and Consumption, 2023)

Wild coral oocytes are more amenable to low temperature preservation than cultured counterparts - Chiahsin Lin; Cheng-Chia Lin; Fu-Wen Kuo; Sujune Tsai (Marine Environmental Research, 2023)

Gas-phase and PM2.5-bound phthalates in nail salons: characteristics, exposure via inhalation, and influencing factors - Chia-Ling Chang; Hui-Tzu Chen; Chung-Yu Chen; En-Yu Chen; Kuan-Ting Lin; Chien-Cheng Jung (Environmental Science and Pollution Research, 2023)

Plasma Matrix Metalloproeteinase-9 Is Associated with Seizure and Angioarchitecture Changes in Brain Arteriovenous Malformations - Yo-Tsen Liu; Cheng-Chia Lee; Chun-Fu Lin; Hsiu-Mei Wu; Wan-Yuo Guo; Huai-Che Yang; Feng-Chi Chang; Kang-Du Liou; Chung-Jung Lin (Molecular Neurobiology, 2022)

Source apportionment and health effects of particle-bound metals in PM2.5 near a precision metal machining factory - Chia-Hua Lin; Chia-Hsiang Lai; Tsang-Hsien Hsieh; Cheng-Yun Tsai (Air Quality, Atmosphere & Health, 2022)

Potential Plasticity of Artificial Feed Preference in Juvenile Pharaoh Cuttlefish (Sepia pharaonis) Through Progressive Training Programs - Chia-Huan Ma; Chih-Hung Lin; Yung-Cheng Chang; Hung-Tai Lee; Chyng-Hwa Liou; Te-Hua Hsu (Frontiers in Marine Science, 2022)
The cuttlefish is a commercially important marine species across the world; however, due to the lack of appropriate artificial feed, there is limited future aquaculture development of the cuttlefish. We proposed a novel process comprising (1) feed preference tests and (2) progressive training programs. Through this process, artificial diets can become more suitable for pharaoh cuttlefish ( Sepia pharaonis ). Feed preference tests (based on vision, touch, and smell) revealed that pharaoh cuttlefish preferred rod-shaped feed to flat rod-shaped or ball-shaped feed, moist feed over dry feed (DF), and DF with agar coating to DF without agar coating. Without olfactory training, some cuttlefish refused to eat artificial feed and eventually died. Through progressive training programs (3- and 6-week programs), a survival rate of >80% was achieved. Although the artificial diets examined in this study resulted in a lower conversion ratio for S. pharaonis than for fresh shrimp, available artificial feed can potentially be adopted for cuttlefish aquaculture through the use of our progressive training program.

Towards a rapid assessment of highway slope disasters by using multidisciplinary techniques - Meng-Chia Weng; Cheng-Han Lin; Wen-Jie Shiu; Wei-An Chao; Chia-Chi Chiu; Ching-Fang Lee; Wei-Kai Huang; Che-Ming Yang (Landslides, 2022)
Mega-earthquakes and extreme climate events accompanied by intrinsic fragile geology lead to numerous landslides along mountain highways in Taiwan, causing enormous life and economic losses. In this study, a system for rapid slope disaster information integration and assessment is proposed with the aim of providing information on landslide occurrence, failure mechanisms, and subsequent landslide-affected areas to the highway authority rapidly. The functionality of the proposed system is deployed into three units: (1) geohazard rapid report (GeoPORT I), (2) multidisciplinary geological survey report (GeoPORT II), and (3) site-specific landslide simulation report (GeoPORT III). After landslide occurrence, the seismology-based monitoring network rapidly provides the initial slope disaster information, including preliminary location, event magnitude, earthquake activity, and source dynamics, within an hour. Within 3 days of the landslide, a multidisciplinary geological survey is conducted to collect high-precision topographical, geological, and remote-sensing data to determine the possible failure mechanism. After integrating the aforementioned information, a full-scale three-dimensional landslide simulation based on the discrete element method is performed within 10 days to reveal the failure process and to identify the areas potentially affected by subsequent disasters through scenario modeling. Overall, the proposed system can promptly provide comprehensive and objective information to relevant authorities after the event occurrence for hazard assessment. The proposed system was validated using a landslide event in the Central Cross-Island Highway of Taiwan.

Review and Future Perspective of Geophysical Methods Applied in Nearshore Site Characterization - Chia-Cheng Tsai; Chun-Hung Lin (Journal of Marine Science and Engineering, 2022)
Seabed surveying is the basis of engineering development in shallow waters. At present, geophysical survey methods mainly utilize sonars for qualitative surveying, which requires the calibration of the results found through in situ drilling and sampling. Among them, the parameters required for engineering designs are obtained from either in situ tests or laboratory experiments of soil samples retrieved from drilling. However, the experience from onshore applications shows that the physical quantities obtained through quantitative geophysical survey methods for shallow waters can be indirectly used to estimate engineering parameters or directly as parameters for engineering evaluation, which has high application potential. This review analyzes various geophysical survey methods for nearshore site characterization (i.e., side-scan sonar, single/multi- beam sonar, sub-bottom profiler, seismic reflection method, and underwater magnetometer) and challenges in their application, and introduces quantitative geophysical survey methods (including the underwater seismic refraction method, seismic surface wave method and underwater electrical resistivity tomography) that are worth focusing on for future development. Three application difficulties have been identified, namely, the lack of operational efficiency, appropriate operational equipment and systems, and sufficient guidance for experimental shallow sea applications. It is hoped that comprehensive discussion of these challenges will increase awareness leading to engineering improvements in the surveying and measuring capabilities in shallow waters, further reducing the risk of geotechnical hazards.

Rac1 and Akt Exhibit Distinct Roles in Mediating Aβ-Induced Memory Damage and Learning Impairment - Kuan-Chung Cheng; Ying-Hao Chen; Chia-Lin Wu; Wang-Pao Lee; Chun Hei Antonio Cheung; Hsueh-Cheng Chiang (Molecular Neurobiology, 2021)

Assessment of climate change effects on alpine summit vegetation in the transition of tropical to subtropical humid climate - Chu-Chia Kuo; Yu Su; Ho-Yih Liu; Cheng-Tao Lin (Plant Ecology, 2021)

Performance Comparison of the Deep Learning and the Human Endoscopist for Bleeding Peptic Ulcer Disease - Hsu-Heng Yen; Ping-Yu Wu; Pei-Yuan Su; Chia-Wei Yang; Yang-Yuan Chen; Mei-Fen Chen; Wen-Chen Lin; Cheng-Lun Tsai; Kang-Ping Lin (Journal of Medical and Biological Engineering, 2021)
Purpose Management of peptic ulcer bleeding is clinically challenging. Accurate characterization of the bleeding during endoscopy is key for endoscopic therapy. This study aimed to assess whether a deep learning model can aid in the classification of bleeding peptic ulcer disease. Methods Endoscopic still images of patients ( n = 1694) with peptic ulcer bleeding for the last 5 years were retrieved and reviewed. Overall, 2289 images were collected for deep learning model training, and 449 images were validated for the performance test. Two expert endoscopists classified the images into different classes based on their appearance. Four deep learning models, including Mobile Net V2, VGG16, Inception V4, and ResNet50, were proposed and pre-trained by ImageNet with the established convolutional neural network algorithm. A comparison of the endoscopists and trained deep learning model was performed to evaluate the model’s performance on a dataset of 449 testing images. Results The results first presented the performance comparisons of four deep learning models. The Mobile Net V2 presented the optimal performance of the proposal models. The Mobile Net V2 was chosen for further comparing the performance with the diagnostic results obtained by one senior and one novice endoscopists. The sensitivity and specificity were acceptable for the prediction of “normal” lesions in both 3-class and 4-class classifications. For the 3-class category, the sensitivity and specificity were 94.83% and 92.36%, respectively. For the 4-class category, the sensitivity and specificity were 95.40% and 92.70%, respectively. The interobserver agreement of the testing dataset of the model was moderate to substantial with the senior endoscopist. The accuracy of the determination of endoscopic therapy required and high-risk endoscopic therapy of the deep learning model was higher than that of the novice endoscopist. Conclusions In this study, the deep learning model performed better than inexperienced endoscopists. Further improvement of the model may aid in clinical decision-making during clinical practice, especially for trainee endoscopist.

Detection of Vestibular Schwannoma on Triple-parametric Magnetic Resonance Images Using Convolutional Neural Networks - Tzu-Hsuan Huang; Wei-Kai Lee; Chih-Chun Wu; Cheng-Chia Lee; Chia-Feng Lu; Huai-Che Yang; Chun-Yi Lin; Wen-Yuh Chung; Po-Shan Wang; Yen-Ling Chen; Hsiu-Mei Wu; Wan-You Guo; et al. (Journal of Medical and Biological Engineering, 2021)
Purpose The first step in typical treatment of vestibular schwannoma (VS) is to localize the tumor region, which is time-consuming and subjective because it relies on repeatedly reviewing different parametric magnetic resonance (MR) images. A reliable, automatic VS detection method can streamline the process. Methods A convolutional neural network architecture, namely YOLO-v2 with a residual network as a backbone, was used to detect VS tumors from MR images. To heighten performance, T1-weighted–contrast-enhanced, T2-weighted, and T1-weighted images were combined into triple-channel images for feature learning. The triple-channel images were cropped into three sizes to serve as input images of YOLO-v2. The VS detection effectiveness levels were evaluated for two backbone residual networks that downsampled the inputs by 16 and 32. Results The results demonstrated the VS detection capability of YOLO-v2 with a residual network as a backbone model. The average precision was 0.7953 for a model with 416 × 416-pixel input images and 16 instances of downsampling, when both the thresholds of confidence score and intersection-over-union were set to 0.5. In addition, under an appropriate threshold of confidence score, a high average precision, namely 0.8171, was attained by using a model with 448 × 448-pixel input images and 16 instances of downsampling. Conclusion We demonstrated successful VS tumor detection by using a YOLO-v2 with a residual network as a backbone model on resized triple-parametric MR images. The results indicated the influence of image size, downsampling strategy, and confidence score threshold on VS tumor detection.

Characterization Of Secondary Metabolites From The Rhizome Of Cynara Scolymus And Their Antioxidant Properties - Chia-Lin Lee; Kuo-Chen Liao; Chien-Chih Chen; Yen-An Lin; Tung-Ying Wu; Yun-Lian Jhan; Chao-Jung Chen; Juan-Cheng Yang; Yang-Chang Wu (Natural Product Research, 2021)

Proton Pump Inhibitor Exposure and Acute Myocardial Infarction Risk: A Nested Cohort Study - Hsiang-Jung Tseng; Chih-Ming Cheng; Shih-Jen Tsai; Wei-Chen Lin; Ya-Mei Bai; Chia-Fen Tsai; Tung-Ping Su; Cheng-Ta Li; Tzeng-Ji Chen; Mu-Hong Chen (Cardiovascular Toxicology, 2021)

Cabbage defense response provoked by Trichoderma Th-LAAO - Chia-Min Liu; Shu-Ying Liu; Chuan-Kai Liao; Chaur-Tsuen Lo; Kuo-Chih Lin; Kou-Cheng Peng (Archives of Microbiology, 2021)

Changes in arthropod community but not plant quality benefit a specialist herbivore on plants under reduced water availability - Po-An Lin; Chia-Ming Liu; Jia-Ang Ou; Cheng-Han Sun; Wen-Po Chuang; Chuan-Kai Ho; Natsuko Kinoshita; Gary W. Felton (Oecologia, 2021)

Protective Effect of (−)Epigallocatechin-3-gallate on Rotenone-Induced Parkinsonism-like Symptoms in Rats - Hsiang-Chien Tseng; Mao-Hsien Wang; Kuo-Chi Chang; Hung-Sheng Soung; Chih-Hsiang Fang; Yi-Wen Lin; Keng-Yuan Li; Chih-Chuan Yang; Cheng-Chia Tsai (Neurotoxicity Research, 2020)

Chemical fingerprint and source apportionment of PM2.5 in highly polluted events of southern Taiwan - Huazhen Shen; Tsung-mou Yang; Chun-chung Lu; Chung-shin Yuan; Chung-Hsuang Hung; Chi-tsan Lin; Chia-wei Lee; Guohua Jing; Gongren Hu; Kuo-cheng Lo (Environmental Science and Pollution Research, 2020)

Comparative Study of Regulations of Devices for Aesthetic Purposes: US, European Union, China, and Taiwan - Mei-Fen Chen; Cheng-Lun Tsai; Yung-Hsin Chen; Cheng-Ning Wu; Ching Chou; Chia-Hung Chien; Pei-Weng Tu; Tsair Kao; Kang-Ping Lin (Journal of Medical and Biological Engineering, 2020)

Leveraging complementary computational models for prioritizing chemicals of developmental and reproductive toxicity concern: an example of food contact materials - Chun-Wei Tung; Hsien-Jen Cheng; Chia-Chi Wang; Shan-Shan Wang; Pinpin Lin (Archives of Toxicology, 2020)

Failure mechanism of a mudstone slope embedded with steep anti-dip layered sandstones: case of the 2016 Yanchao catastrophic landslide in Taiwan - Cheng-Han Lin; Ching Hung; Meng-Chia Weng; Ming-Lang Lin; Ryosuke Uzuoka (Landslides, 2019)

An Adult Drosophila Glioma Model for Studying Pathometabolic Pathways of Gliomagenesis - Kuan-Cheng Chi; Wen-Chiuan Tsai; Chia-Lin Wu; Tzu-Yang Lin; Dueng-Yuan Hueng (Molecular Neurobiology, 2019)

PARK14 (D331Y) PLA2G6 Causes Early-Onset Degeneration of Substantia Nigra Dopaminergic Neurons by Inducing Mitochondrial Dysfunction, ER Stress, Mitophagy Impairment and Transcriptional Dysregulation in a Knockin Mouse Model - Ching-Chi Chiu; Chin-Song Lu; Yi-Hsin Weng; Ying-Ling Chen; Ying-Zu Huang; Rou-Shayn Chen; Yi-Chuan Cheng; Yin-Cheng Huang; Yu-Chuan Liu; Szu-Chia Lai; Kun-Jun Lin; Yan-Wei Lin; et al. (Molecular Neurobiology, 2019)

Conditional Overexpression of rtn4al in Muscle of Adult Zebrafish Displays Defects Similar to Human Amyotrophic Lateral Sclerosis - Cheng-Yung Lin; Po-Hsiang Zhang; You-Jei Chen; Chia-Lun Wu; Huai-Jen Tsai (Marine Biotechnology, 2019)

Adenosine Augmentation Evoked by an ENT1 Inhibitor Improves Memory Impairment and Neuronal Plasticity in the APP/PS1 Mouse Model of Alzheimer’s Disease - Chia-Chia Lee; Ching-Pang Chang; Chun-Jung Lin; Hsing-Lin Lai; Yu-Han Kao; Sin-Jhong Cheng; Hui-Mei Chen; Yu-Ping Liao; Emilie Faivre; Luc Buée; David Blum; Jim-Min Fang; et al. (Molecular Neurobiology, 2018)

Plasminogen/thrombomodulin signaling enhances VEGF expression to promote cutaneous wound healing - Tsung-Lin Cheng; Po-Ku Chen; Wei-Kai Huang; Cheng-Hsiang Kuo; Chia-Fong Cho; Kuan-Chieh Wang; Guey-Yueh Shi; Hua-Lin Wu; Chao-Han Lai (Journal of Molecular Medicine, 2018)

Web-Based Experience Sharing Platform on Medical Device Incidents for Clinical Engineers in Hospitals - Mei-Fen Chen; Cheng-Lun Tsai; Yung-Hsin Chen; Yu-Wen Huang; Cheng-Ning Wu; Ching Chou; Chia-Hung Chien; Pei-Weng Tu; Tsair Kao; Kang-Ping Lin (Journal of Medical and Biological Engineering, 2018)

Dynamic response of a dip slope with multi-slip planes revealed by shaking table tests - Hung-Hui Li; Cheng-Han Lin; Wei Zu; Chi-Chieh Chen; Meng-Chia Weng (Landslides, 2018)

Identification of a new type tadalafil analogue in a supplement product - Yen-Chun Huang; Hui-Chun Lee; Yun-Lian Lin; Chia-Fen Tsai; Hwei-Fang Cheng (Food Additives & Contaminants: Part A, 2018)

Correction to: Functional near-infrared spectroscopy (fNIRS) brain imaging of multi-sensory integration during computerized dynamic posturography in middle-aged and older adults - Chia-Cheng Lin; Jeffrey W. Barker; Patrick J. Sparto; Joseph M. Furman; Theodore J. Huppert (Experimental Brain Research, 2018)

Sediment control function of river notches - Chia-Hsing Lin; Cheng-Ju Liu; Shih-Hsun Lin; Chjeng-Lun Shieh (Journal of Mountain Science, 2018)

Identification of morin as an agonist of imidazoline I-3 receptor for insulin secretion in diabetic rats - Mang Hung Lin; Chia-Chen Hsu; Jenshinn Lin; Juei-Tang Cheng; Ming Chang Wu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2017)

Chalcone flavokawain B induces autophagic-cell death via reactive oxygen species-mediated signaling pathways in human gastric carcinoma and suppresses tumor growth in nude mice - Chia-Ting Chang; You-Cheng Hseu; Varadharajan Thiyagarajan; Kai-Yuan Lin; Tzong-Der Way; Mallikarjuna Korivi; Jiuun-Wang Liao; Hsin-Ling Yang (Archives of Toxicology, 2017)

Complete nucleotide sequences of M and L RNAs from a new pepper-infecting tospovirus, Pepper chlorotic spot virus - Kuo-Shiou Huang; Chia-Hsing Tai; Ying-Huey Cheng; Shu-Hui Lin; Tsung-Chi Chen; Fuh-Jyh Jan (Archives of Virology, 2017)

Functional near-infrared spectroscopy (fNIRS) brain imaging of multi-sensory integration during computerized dynamic posturography in middle-aged and older adults - Chia-Cheng Lin; Jeffrey W. Barker; Patrick J. Sparto; Joseph M. Furman; Theodore J. Huppert (Experimental Brain Research, 2017)

Anti-apoptotic and Pro-survival Effects of Food Restriction on High-Fat Diet-Induced Obese Hearts - Yi-Yuan Lin; Po-Shiuan Hsieh; Yu-Jung Cheng; Shiu-Min Cheng; Chiao-nan Chen; Chih-Yang Huang; Chia-Hua Kuo; Chung-Lan Kao; Woei-Cherng Shyu; Shin-Da Lee (Cardiovascular Toxicology, 2017)

Isolation and identification of a novel sildenafil analogue adulterant in herbal products - Ya-Tze Lin; Yen-Chun Huang; Hui-Chun Lee; Chen-Hsiang Liao; Yun-Lian Lin; Chia-Fen Tsai; Hwei-Fang Cheng (Food Additives & Contaminants: Part A, 2017)

Identification of a new sildenafil analogue adulterant, desethylcarbodenafil, in a herbal supplement - Yen-Chun Huang; Hui-Chun Lee; Yun-Lian Lin; Ya-Tze Lin; Chia-Fen Tsai; Hwei-Fang Cheng (Food Additives & Contaminants: Part A, 2016)

Characterization and evaluation of Bacillus amyloliquefaciens strain WF02 regarding its biocontrol activities and genetic responses against bacterial wilt in two different resistant tomato cultivars - Chu-Ning Huang; Chan-Pin Lin; Feng-Chia Hsieh; Sook-Kuan Lee; Kuan-Chen Cheng; Chi-Te Liu (World Journal of Microbiology and Biotechnology, 2016)

Associations of TNF-α and IL-6 polymorphisms with osteoporosis through joint effects and interactions with LEPR gene in Taiwan: Taichung Community Health Study for Elders (TCHS-E) - Cheng-Chieh Lin; Tsai-Chung Li; Chiu-Shong Liu; Chuan-Wei Yang; Chih-Hsueh Lin; Jen-Hao Hsiao; Nai-Hsin Meng; Wen-Yuan Lin; Li-Na Liao; Chia-Ing Li; Fang-Yang Wu (Molecular Biology Reports, 2016)

Allergy symptoms, serum total immunoglobulin E, and risk of head and neck cancer - Hsiao-Chen Liao; Shang-Yin Wu; Chun-Yen Ou; Jenn-Ren Hsiao; Jehn-Shyun Huang; Sen-Tien Tsai; Cheng-Chih Huang; Tung-Yiu Wong; Wei-Ting Lee; Ken-Chung Chen; Sheen-Yie Fang; Jiunn-Liang Wu; et al. (Cancer Causes & Control, 2016)

Identification of a new tadalafil analogue, dipropylaminopretadalafil, in a dietary supplement - Yen-Chun Huang; Hui-Chun Lee; Yun-Lian Lin; Chia-Fen Tsai; Hwei-Fang Cheng (Food Additives & Contaminants: Part A, 2016)

Humic acids enhance the microbially mediated release of sedimentary ferrous iron - Chun-Han Chang; Chia-Cheng Wei; Li-Hung Lin; Tzu-Hsuan Tu; Vivian Hsiu-Chuan Liao (Environmental Science and Pollution Research, 2016)

Separation and identification of a novel tadalafil analogue adulterant in a dietary supplement - Yen-Chun Huang; Hui-Chun Lee; Yun-Lian Lin; Chia-Ying Li; Chia-Fen Tsai; Hwei-Fang Cheng (Food Additives & Contaminants: Part A, 2015)

High-Performance Multiclass Classification Framework Using Cloud Computing Architecture - Feng-Sheng Lin; Chia-Ping Shen; Chia-Hung Liu; Han Lin; Chi-Ying F. Huang; Cheng-Yan Kao; Feipei Lai; Jeng-Wei Lin (Journal of Medical and Biological Engineering, 2015)

Analysis of non-separable spatiotemporal data with application to enterovirus study in Taiwan - Pei-Sheng Lin; Chao A. Hsiung; Chia-Wei Cheng (Environmental and Ecological Statistics, 2014)

Denbinobin upregulates miR-146a expression and attenuates IL-1β-induced upregulation of ICAM-1 and VCAM-1 expressions in osteoarthritis fibroblast-like synoviocytes - Chia-Ron Yang; Kao-Shang Shih; Jing-Ping Liou; Yi-Wen Wu; I-Ni Hsieh; Hsueh-Yun Lee; Tzu-Cheng Lin; Jyh-Horng Wang (Journal of Molecular Medicine, 2014)

Concentrations of particulates in ambient air, gaseous elementary mercury (GEM), and particulate-bound mercury (Hg(p)) at a traffic sampling site: a study of dry deposition in daytime and nighttime - Guor-Cheng Fang; Yen-Heng Lin; Chia-Ying Chang; Yu-Cheng Zheng (Environmental Geochemistry and Health, 2014)

Cingulum Correlates of Cognitive Functions in Patients with Mild Cognitive Impairment and Early Alzheimer’s Disease: A Diffusion Spectrum Imaging Study - Yi-Cheng Lin; Yao-Chia Shih; Wen-Yih I. Tseng; Yu-Hsiu Chu; Meng-Tien Wu; Ta-Fu Chen; Pei-Fang Tang; Ming-Jang Chiu (Brain Topography, 2014)

Genetic variations in TP53 binding sites are predictors of clinical outcomes in prostate cancer patients - Victor C. Lin; Chao-Yuan Huang; Yung-Chin Lee; Chia-Cheng Yu; Ta-Yuan Chang; Te-Ling Lu; Shu-Pin Huang; Bo-Ying Bao (Archives of Toxicology, 2014)

Application of a web-based remote agro-ecological monitoring system for observing spatial distribution and dynamics of Bactrocera dorsalis in fruit orchards - Joe-Air Jiang; Tzu-Shiang Lin; En-Cheng Yang; Chwan-Lu Tseng; Chia-Pang Chen; Chung-Wei Yen; Xiang-Yao Zheng; Chun-Yi Liu; Ren-Hau Liu; Yu-Fan Chen; Wan-Yi Chang; Cheng-Long Chuang (Precision Agriculture, 2013)

Application of a feature-based approach to debris flow detection by numerical simulation - Chih-Wei Lin; Cheng-Wu Chen; Wen-Ko Hsu; Chia-Yen Chen; Chung-Hung Tsai; Yi-Ping Hung; Wei-Ling Chiang (Natural Hazards, 2013)

Erratum to: Significance of IL-6 in the transition of hormone-resistant prostate cancer and the induction of myeloid-derived suppressor cells - Chun-Te Wu; Ching-Chuan Hsieh; Cheng-Chia Lin; Wen-Cheng Chen; Ji-Hong Hong; Miao-Fen Chen (Journal of Molecular Medicine, 2013)

Aging-related decline in somatosensory inhibition of the human cerebral cortex - Chia-Hsiung Cheng; Yung-Yang Lin (Experimental Brain Research, 2013)

Iron plaque formation and its effect on arsenic uptake by different genotypes of paddy rice - Chia-Hsing Lee; Yi-Cheng Hsieh; Tzu-Huei Lin; Dar-Yuan Lee (Plant and Soil, 2013)

Estrogen stimulates the proliferation of human endometrial cancer cells by stabilizing nucleophosmin/B23 (NPM/B23) - Angel Chao; Chiao-Yun Lin; Chia-Lung Tsai; Swei Hsueh; Ying-Yu Lin; Cheng-Tao Lin; Hung-Hsueh Chou; Tzu-Hao Wang; Chyong-Huey Lai; Hsin-Shih Wang (Journal of Molecular Medicine, 2013)

Glycogen synthase kinase-3β inactivation is an intracellular marker and regulator for endotoxemic neutrophilia - Tsan-Tzu Yang; Chia-Ling Chen; Wei-Chieh Lin; Yee-Shin Lin; Po-Chun Tseng; Chia-Yuan Hsieh; Yu-Hong Chen; Wei-Ching Huang; Cheng-Chieh Tsai; Chi-Yun Wang; Chi-Chang Shieh; Chiou-Feng Lin (Journal of Molecular Medicine, 2013)

The joint effect of cigarette smoking and polymorphisms on LRP5, LEPR, near MC4R and SH2B1 genes on metabolic syndrome susceptibility in Taiwan - Chuan-Wei Yang; Chia-Ing Li; Chiu-Shong Liu; Da-Tian Bau; Chih-Hsueh Lin; Wen-Yuan Lin; Tsai-Chung Li; Cheng-Chieh Lin (Molecular Biology Reports, 2013)

Significance of IL-6 in the transition of hormone-resistant prostate cancer and the induction of myeloid-derived suppressor cells - Chun-Te Wu; Ching-Chuan Hsieh; Cheng-Chia Lin; Wen-Cheng Chen; Ji-Hong Hong; Miao-Fen Chen (Journal of Molecular Medicine, 2012)

Niacin improves ischemia-induced neovascularization in diabetic mice by enhancement of endothelial progenitor cell functions independent of changes in plasma lipids - Po-Hsun Huang; Chih-Pei Lin; Chao-Hung Wang; Chia-Hung Chiang; Hsiao-Ya Tsai; Jia-Shiong Chen; Feng-Yen Lin; Hsin-Bang Leu; Tao-Cheng Wu; Jaw-Wen Chen; Shing-Jong Lin (Angiogenesis, 2012)

Caffeine’s effect on intermittent sprint cycling performance with different rest intervals - Chia-Lun Lee; Ching-Feng Cheng; Jung-Charng Lin; Hsin-Wei Huang (European Journal of Applied Physiology, 2012)

Identification of furo[3′, 2′:3,4]naphtho[1,2-d]imidazole derivatives as orally active and selective inhibitors of microsomal prostaglandin E2 synthase-1 (mPGES-1) - Chih-Hua Tseng; Cherng-Chyi Tzeng; Pin-Keng Shih; Chia-Ning Yang; You-Chung Chuang; Shin-I Peng; Chang-Sheng Lin; Jih-Pyang Wang; Chih-Mei Cheng; Yeh-Long Chen (Molecular Diversity, 2012)

Determination of critical power in trained rowers using a three-minute all-out rowing test - Ching-Feng Cheng; Yi-Shan Yang; Hui-Mei Lin; Chia-Lun Lee; Chun-Yi Wang (European Journal of Applied Physiology, 2012)

Characterization of mitochondrial genome of Formosan sambar (Rusa unicolor swinhoei) - Chia-Hsuan Chen; Hsiu-Lin Huang; Mu-Tzu Chang; Li-Chia Chiang; Shih-Lin Cheng; Bing-Tsan Liu; Chih-Hua Wang; Ming-Che Wu; Mu-Chiou Huang (Biologia, 2011)

Molecular and morphological evidences reveal a cryptic species in the Vinaceous Rosefinch Carpodacus vinaceus (Fringillidae; Aves) - Hsu‐Chun Wu; Rong‐Chien Lin; Hsin‐Yi Hung; Chia‐Fen Yeh; Jui‐Hua Chu; Xiao‐Jun Yang; Chiou‐Ju Yao; Fa‐Sheng Zou; Cheng‐Te Yao; Shou‐Hsien Li; Fu‐Min Lei (Zoologica Scripta, 2011)
Wu, H.‐C., Lin, R.‐C., Hung, H.‐Y., Yeh, C.‐F., Chu, J.‐H., Yang, X.‐J., Yao, C.‐J., Zou, F.‐S., Yao, C.‐T., Li, S.‐H. & Lei, F.‐M. (2011). Molecular and morphological evidences reveal a cryptic species in the Vinaceous Rosefinch Carpodacus vinaceus (Fringillidae; Aves). — Zoologica Scripta, 40 , 468–478. The Vinaceous Rosefinch ( Carpodacus vinaceus ) is endemic in East Asia with two recognized subspecies – C. v. vinaceus , distributed along the eastern edge of the Tibetan Plateau and the Himalayas, and C. v. formosanus , restricted to Taiwan’s Central Mountain Range. As reflected in a controversial taxonomic history, this vastly disjunctive distribution pattern suggests that the subspecies, having been isolated from each other for a long time, might have diverged, challenging the current taxonomic treatment and calling for possible species delimitation. Sequences of two mitochondrial fragments (mtDNA) and two Z‐linked nuclear loci (zDNA) were used to reconstruct the intraspecific phylogeny of C. vinaceous . The mtDNA tree shows that the two subspecies of the vinaceous rosefinch form two exclusively monophyletic clades. All but one zDNA sequences from the nominate subspecies and C. v. formosanus also formed exclusively monophyletic clades (the exceptional zDNA sequence from C. v. vinaceous formed a weakly supported clade with two outgroup species). Moreover, by conducting quantitative comparisons of morphometric traits and male plumage coloration, we found that the two subspecies exhibit distinguishable morphological differences. All the evidence therefore suggests that C. v. formosanus is a cryptic species and that its taxonomic status should be restored to full species. Molecular dating suggests that the two sibling rosefinches split 1.7 ± 0.2 million years ago, providing a point estimate for the historical connectivity of biota between eastern Tibet‐Himalayas and montane Taiwan.

Effect of caffeine ingestion after creatine supplementation on intermittent high-intensity sprint performance - Chia-Lun Lee; Jung-Charng Lin; Ching-Feng Cheng (European Journal of Applied Physiology, 2011)

Ectopic expression of an EAR motif deletion mutant of SlERF3 enhances tolerance to salt stress and Ralstonia solanacearum in tomato - I-Chun Pan; Chia-Wen Li; Ruey-Chih Su; Chiu-Ping Cheng; Choun-Sea Lin; Ming-Tsair Chan (Planta, 2010)

Two genetic divergence centers revealed by chloroplastic DNA variation in populations of Cinnamomum kanehirae Hay - Dai-Chang Kuo; Chia-Chia Lin; Kuo-Chieh Ho; Yu-Pin Cheng; Shih-Ying Hwang; Tsan-Piao Lin (Conservation Genetics, 2010)

Rejecting strictly allopatric speciation on a continental island: prolonged postdivergence gene flow between Taiwan ( Leucodioptron taewanus , Passeriformes Timaliidae) and Chinese ( L. canorum canorum ) hwameis - JING-WEN LI; CAROL K. L. YEUNG; PI-WEN TSAI; RONG-CHIEN LIN; CHIA-FEN YEH; CHENG-TE YAO; LIANXIAN HAN; LE MANH HUNG; PING DING; QISHAN WANG; SHOU-HSIEN LI (Molecular Ecology, 2010)

Empirical Models to Predict Parsimoniously the Mass and Number Concentrations of Ultrafine Particulate in Ambient Atmosphere - Chia-Pin Chio; Man-Ting Cheng; Yu-Chi Lin; Chung-Min Liao (Bulletin of Environmental Contamination and Toxicology, 2009)

Dry deposition study by using dry deposition plate and water surface sampler in Shalu, central Taiwan - Chia-Chun Chu; Guor-Cheng Fang; Jhy-Cherng Chen; I-Lin Yang (Environmental Monitoring and Assessment, 2008)

Seasonal change and correlation with environmental parameters for 2-MIB in Feng-Shen Reservoir, Taiwan - Shu-Chu Tung; Tsair-Fuh Lin; Feng-Cheng Yang; Chia-Lin Liu (Environmental Monitoring and Assessment, 2008)

Compositions and source apportionments of atmospheric aerosol during Asian dust storm and local pollution in central Taiwan - Man-Ting Cheng; Wei-Chun Chou; Chia-Pin Chio; Shih-Chieh Hsu; Yi-Ru Su; Pei-Hsuan Kuo; Ben-Jei Tsuang; Shuen-Hsin Lin; Charles C.-K. Chou (Journal of Atmospheric Chemistry, 2008)

A rice phenomics study—phenotype scoring and seed propagation of a T-DNA insertion-induced rice mutant population - Chyr-Guan Chern; Ming-Jen Fan; Su-May Yu; Ai-Ling Hour; Po-Chang Lu; Yao-Cheng Lin; Fu-Jin Wei; Sheng-Chung Huang; Shu Chen; Ming-Hsing Lai; Ching-Shan Tseng; Hsing-Mu Yen; et al. (Plant Molecular Biology, 2007)

A fine physical map of the rice chromosome 5 - Chia-Hsiung Cheng; Mei-Chu Chung; Shu-Mei Liu; Shi-Kuang Chen; Fang-Yi Kao; Shu-Jen Lin; Shin-Hsin Hsiao; I-Chieh Tseng; Yue-Ie C. Hsing; Hong-Pang Wu; Ching-San Chen; Jei-Fu Shaw; et al. (Molecular Genetics and Genomics, 2005)

Ferredoxin from sweet pepper (Capsicum annuum L.) intensifying harpinpss-mediated hypersensitive response shows an enhanced production of active oxygen species (AOS) - Badri Venkata Dayakar; Hao-Jan Lin; Cheng-Hsien Chen; Mang-Jye Ger; Bor- Heng Lee; Chia-Hwei Pai; David Chow; Hsiang-En Huang; Shaw-Yhi Hwang; Mei-Chu Chung; Teng-Yung Feng (Plant Molecular Biology, 2003)